Bioeconomic Indices of Broiler Chicks Fed Varying Ratios of Cassava Peel/Bovine Blood - Onyimonyi, A.E.; Ugwu, S.O.C. (International Journal of Poultry Science, 2007)
An experiment was conducted to evaluate the performance of early growing broilers (2-6 weeks old) fed diets in which cassava peel/bovine blood mixed at varying ratios replaced 50 percent of the soyabean meal in the control Diet. One hundred and twenty broiler chicks were randomly allotted to six treatments replicated twice in a completely randomized design. Diet 1 served as the control, while Diets 2, 3, 4, 5 and 6 had cassava peel/bovine blood mixed in the ratios of 1:1; 1:2; 1:3; 2:1; and 3:1; respectively. The feeding trial lasted for 28 days. Results showed that the effect of treatments on Average Daily Feed Intake (ADFI) was significant (P0.05). Economic analysis showed that feed cost per bird was lower in the cassava/bovine blood based groups. Revenue from these groups were also higher than in the control. Benefit from birds on Diet 4 (1:3 ratio of cassava peel/bovine blood) was highest- 495.62 as against 385.23; 413.28; 459.95; 462.43 and 445.32 for birds on the control, Diets 1, 2, 3, 5 and 6 respectively. It was concluded that feeding early growing broilers cassava peel/bovine blood can effectively replace 50 percent of soyabean meal in the control without any adverse effect on the performance of the birds, while cassava peel/bovine blood at the 1: 3 rate gave the highest economic return.